Research on the mechanical property and failure mechanism of the dieless clinched joints of various aluminum alloys. (July 2022) - Qin, Denglin; Chen, Chao
Highlights: The failure mechanism of various joints was revealed from a micro and macro view. The novel dieless clinched joint can withstand large load before failure. The dieless clinching process can be used to join Al5052, Al5182 and Al6061 sheets. The mechanical properties of various joints were obtained and analyzed. Abstract: This paper dealt with the mechanical property and failure mechanism of the dieless clinched joints of AL5052, AL5182 and AL6061 aluminum alloys. The cross-tensile test and lap-shear test were executed to assess the mechanical properties of various aluminum joints. Detailed fracture surface analyses were also performed to reveal the failure mechanisms of various aluminum alloy joints in different failure tests from both macro and micro perspectives. The forming curves, key geometrical parameters, static loads, absorbed energy, and fracture morphology of various aluminum alloy joints were obtained and analyzed. From the results, the AL6061 joint exhibits the most superior mechanical properties, i.e., the optimum static load and energy absorption, whereas the AL5182 joint exhibits the worst mechanical properties. Besides, although the macroscopic failure mode of various aluminum joints is the same, i.e., neck fracture mode, the joint microscopic failure mechanism varies with the types of sheet material and failure test.